Ground Water Quality Evaluation with Using WQI of Selected wells in Mandali Area, Diyala Governorate, East Iraq - Al-Mashhadani, Reham Basim; Al-Kubaisi, Qusai Y. (Iraqi Journal of Science, 2023)
Groundwater is necessary to ensure the safety of Mandali's water supply. Groundwater samples were collected from various parts of the city for this study. Two aquifers have been identified: the first is a free bed made up of Quaternary deposits. The second is the primary bed that conveys water,  belonging to the Bai Hassan Formation. Nineteen groundwater samples were collected from wells and examined for physicochemical parameters in the current study during October 2021. Samples were analyzed for main cations Ca2+, Mg2+, Na+, and K+;  anions HCO3- , SO42- , Cl- and NO3-,  pH, Electrical Conductivity, and Total Dissolved Solids. Results indicated that the Samples water is neutral to slightly alkaline. The TDS classifications show that the groundwater samples are classified as fresh to slightly fresh water. All water samples are severely mineralized, except sample W17 which is highly mineralized due to the water feeding from the deep aquifer of Bai Hassan formation. Dominant cation is Na+ followed by Ca2+, Mg2+ then K+, whereas dominant anion SO42 ̶  followed by Cl¯ then HCO3¯. The water type of  8 samples 42% is NaCl type, seven samples 37% is MgSO4 type, three samples 16% is Na2SO4 type, and 1 sample 5% is CaSO4. The diversity in water is because the sediments of the Quaternary age derived from neighboring formations such as Fatha and other formations. According to Piper's diagram, Groundwater samples are mostly earth alkaline water with an increased amount of alkali,  high sulfate and chloride. The groundwater in the study area has a wide range of WQI ranging from excellent (W17) while classified as good water (W1, W3, W4, W5, W6, W7, W8, W9, W11, W12, W13, W14, W16, W18, W19) and classified as Poor water (W2, W10, W15) because of the high values of WQI values computed.